2000
DOI: 10.1037/0022-3514.78.4.764
|View full text |Cite
|
Sign up to set email alerts
|

Social comparisons of income in one's community: Evidence from national surveys of income and happiness.

Abstract: Two studies provide evidence for social comparison effects of income on subjective well-being (SWB). The 1st study of 7,023 persons from nationally representative samples in the United States shows that the range and skew of the income distribution in a community affects a person's happiness, as predicted by range-frequency theory. The 2nd study of 8 nations over a period of 25 years shows that decreasing the skew (inequality) of the income distribution in a country increases average national SWB. Both studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
211
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(231 citation statements)
references
References 13 publications
15
211
1
4
Order By: Relevance
“…Evidence suggests that the experience of poverty and deprivation have a significant bearing on subjective well-being (Hagerty 2000;Diener et al 1999;Gudmundsdottir 2013). At the same time, studies hint at a variation in the extent to which economic hardship affects well-being; some people are more resilient in the face of economic hardship than others.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence suggests that the experience of poverty and deprivation have a significant bearing on subjective well-being (Hagerty 2000;Diener et al 1999;Gudmundsdottir 2013). At the same time, studies hint at a variation in the extent to which economic hardship affects well-being; some people are more resilient in the face of economic hardship than others.…”
Section: Introductionmentioning
confidence: 98%
“…Hagerty (2000) found that when personal income was statistically controlled, individuals living in higher-income areas in the United States were lower in happiness than people living in lower-income areas. This suggests that wealthy individuals are fortunate if they live in middle-class areas rather than in wealthy enclaves.…”
Section: Negative Outcomes Of Wealth and Materialismmentioning
confidence: 99%
“…Rank effects have been observed for the evaluation of different entities, ranging from psychophysical stimuli (Parducci & Perrett, 1971) to cognitive and social quantities such as satisfaction with body image (Wedell, Santoyo, & Pettibone, 2005), wages (Brown, Gardner, Oswald, & Qian, 2008;Hagerty, 2000), health and well-being (Boyce, Brown, & Moore, 2010;Boyce & Wood, in press;Wood, Boyce, Moore, & Brown, 2012), gratitude (Wood, Brown, & Maltby, 2011), satisfaction with educational provision (Brown, Wood, Ogden, & Maltby, 2015), fairness of sentencing (Aldrovandi, Wood, & Brown, 2013), indebtedness (Aldrovandi, Wood, Maltby, & Brown, in press), and perception of health risks due to alcohol consumption (Wood, Brown, & Maltby, 2012). However, the implications of the rank-based models have not been explored within the literature on food evaluation or within the marketing and consumer research literature more generally (although see Niedrich et al, 2001;Niedrich et al, 2009).…”
Section: Social Norms and Rank-based Nudgingmentioning
confidence: 99%